Some new diagnostics of multicollinearity in linear regression model - Ullah, Muhammad Imdad; Aslam, Muhammad; Altaf, Saima; Ahmed, Munir (Penerbit Universiti Kebangsaan Malaysia, 2019)
The problem of multicollinearity compromises the numerical stability of the regression coefficient estimate and cause some serious problem in validation and interpretation of the model. In this paper, we propose two new collinearity diagnostics for the detection of collinearity among regressors, based on coefficient of determination and adjusted coefficient of determination from auxiliary regression of regressors. A Monte Carlo simulation study has been conducted to compare the existing and proposed collinearity diagnostic tests. Comparison of diagnostics on some existing collinear data are also made.